Analisis Biaya Produksi dan Pendapatan Usahatani Nanas (Ananas Comosus L. Merr) dengan Pemanfaatan Sistem Tanaman Sela (Studi Kasus Desa Senuro Barat Kecamatan Tanjung Batu Kabupaten Ogan Ilir) - Afifuddin; Budi Fachrudin; Muhammad Andri Zuliansyah (KaliAgri Journal, 2023)
This study aims to determine how much production costs incurred and the income earned by farmers in pineapple farming with the utilization relay cropping. This research was conducted in Senuro Barat Village, Tanjung Batu District, Ogan Ilir Regency by considering that Senuro Barat Village is one of the villages where most of the farmers work as pineapple farmers. The research method uses the case study method. Data collection methods used in this study include primary data and secondary data. Sampling is done by simple random sampling, which is 30 samples from 325 of the total population of pineapple farmers. The results showed that the total cost of production of pineapple farming with the utilization relay cropping per hectare per season in West Senuro Village, Tanjung Batu District, Ogan Ilir Regency amounted to Rp.18,854,112/year. Pineapple farmer receipts for grade A amounted to Rp. 112,636,520 and grade B amounted to 71,868,812. Pineapple farmers' income for grade A amounted to Rp 93,782,408/year and grade B amounted to Rp 53,014,700/year. Furthermore, the R/C ratio value obtained for grade A amounted to 4.97 and grade B amounted to 2.81. This shows that pineapple farming is feasible because the R/C ratio value is >1.